2007
DOI: 10.1016/j.jacc.2007.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Closure Devices

Abstract: Vascular closure devices (VCDs) introduce a novel means for improving patient comfort and accelerating ambulation after invasive cardiovascular procedures performed via femoral arterial access. Vascular closure devices have provided simple, rapid, and reliable hemostasis in a variety of clinical settings. Despite more than a decade of development, however, VCD utilization has neither been routine in the U.S. nor around the world. Their limited adoption reflects concerns of higher costs for cardiac procedures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
124
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(128 citation statements)
references
References 56 publications
(103 reference statements)
0
124
1
3
Order By: Relevance
“…3,14,17 The largest study to date, from the American College of Cardiology-National Cardiovascular Date Registry (ACC-NCDR) registry, evaluated 166 680 men and women undergoing diagnostic and interventional cardiac procedures from 1998 to 2001 and showed that female gender was a strong predictor of VC (relative risk, 2.18; PϽ0.001) and associated death (relative risk, 2.59; PϽ0.001) compared with men. 11 A follow-up study from the same authors evaluating data on 13 878 catheterization patients (5225 women) in 2003 revealed an improvement in VC show decreasing rates of bleeding/VC for both men and women including crude and adjusted rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,14,17 The largest study to date, from the American College of Cardiology-National Cardiovascular Date Registry (ACC-NCDR) registry, evaluated 166 680 men and women undergoing diagnostic and interventional cardiac procedures from 1998 to 2001 and showed that female gender was a strong predictor of VC (relative risk, 2.18; PϽ0.001) and associated death (relative risk, 2.59; PϽ0.001) compared with men. 11 A follow-up study from the same authors evaluating data on 13 878 catheterization patients (5225 women) in 2003 revealed an improvement in VC show decreasing rates of bleeding/VC for both men and women including crude and adjusted rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Observational studies demonstrate that female gender is a powerful predictor of bleeding/VC in patients undergoing both diagnostic catheterization and percutaneous coronary intervention (PCI) [5][6][7][8][9][10][11][12] by means of the femoral approach. Over the last decade, several procedural-related improvements, such as use of smaller sheaths, successful use of vascular closure devices (VCD), 3,11,13,14 better access techniques, 15 and improved antithrombotic therapies, 16 have led to an overall decline in complication rates. 14,17,18 Clinical Perspective on p 429…”
mentioning
confidence: 99%
“…The 30 days access-site related complication rates were remarkably low in both the groups in this study [4]. However, most of the pivotal studies comparing vascular closure devices and standard manual pressure comprised of small numbers and were underpowered [5]. This limitation in sample size has prompted researchers to meta-analyse the available data.…”
Section: Discussionmentioning
confidence: 79%
“…For example they may increase the risk of hematoma and pseudoaneurysm formation (26,35,36,(41)(42)(43). Moreover, early device failure rates and their impact on vascular access site complications are not always clearly reported in these trials but may decrease after the initial learning curve.…”
Section: Impact Of Vascular Closure Devices On Vascular Access Site Cmentioning
confidence: 99%
“…Moreover, early device failure rates and their impact on vascular access site complications are not always clearly reported in these trials but may decrease after the initial learning curve. Recently, data with the last generation of vascular closure devices suggest that their use may decrease vascular complications but these points had to be confirmed once again by large randomized trials because it maybe simply reflects a better patient selection and operator experience with these devices over time (4,42,44).…”
Section: Impact Of Vascular Closure Devices On Vascular Access Site Cmentioning
confidence: 99%